Maternal concerns about immunization over 0–24 month children: a qualitative research. (December 2014) - Delkhosh, Marjan; Negarandeh, Reza; Ghasemi, Elham; Rostami, Hossein
<x xml:space="preserve">Abstract</x> The purpose of this qualitative study was to determine the concerns of mothers referred to health center in south Tehran, Iran about immunizing children aged 0–24 months. Data were collected using individual semi-structured interviews and analyzed using content analysis. The mothers' concerns over immunizing their children fell into 5 main categories: (1) "Factors that cause mothers' concerns, " (2) "Factors that influence mothers' concerns, " (3) "Information, education, and communication barriers, " (4) "Informational/educational needs and sources, " and (5) "The necessity of childhood vaccinations." According to study findings, mothers consider immunizing children important and they have enough trust in the health system. A deep understanding of maternal concerns about immunizing their children at 0–24 months allows nurses to reduce mothers' concerns by removing communication barriers and providing appropriate and adequate information.